AKTIVITAS ANTIFUNGI EKSTRAK ETANOL BATANG BINAHONG (Anredera cordifolia (Tenore) Steen.) TERHADAP Candida albicans SERTA SKRINING FITOKIMIA - Eka Kumalasari; Nanik Sulistyani (Universitas Ahmad Dahlan, 2011)
Anredera cordifolia is a plantused as antifungal empirically. This study aims to find out the antifungal activity of ethanol extract of A. cordifolia stem against C. albicans and to identify the chemical subtance groups of the ethanol extract of A. cordifolia. The A. cordifolia stem was extracted by maceration method using ethanol 70 % as solvent. The antifungal assay was done using liquid dilution method with various concentrations of (85; 86; 87; 88; 89; 90% w /v). The mixtures of extract and suspension of C. albicans in CYG (Casein Yeast Glucose) medium and the media were incubated at 37ºC for 18-24 hours to determine Minimum Inhibitor Conceration (MIC). The culture was streaked on SDA (Sabouraud Dextrose Agar) medium to determine Minimum Fungicidal Conceration (MFC). Chromatographic test and tube test were done to identify the chemical substances of A. cordifolia extract. The result showed that the MIC could not be determined because the extract was brownish and turbid while the MFC of A. cordifolia stem ethanolic extract was 86% w /v. The result of the phytochemical screening with tube test and the thin layer chromatography test showed that the extract of A. cordifolia stem contained flavonoids, polyphenols, and saponin.